The Development of Gamification-Based Qur'an Learning Media Using Wordwall at SMK Muhammadiyah 3 Singosari, Indonesia - Sya'roni Al Fajri (Bulletin of Indonesian Islamic Studies, 2025)
This study aims to develop a gamification-based Al-Qur'an learning medium through the Wordwall platform with the theme of Fastabiqul Khoirot for grade X students at SMK Muhammadiyah 3 Singosari. Al-Qur'an learning faces challenges in student engagement due to monotonous teaching methods. This development research uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with a gamification approach that integrates game elements into learning. The resulting product is named "QurFast: Learn Qur'an Fun and Enjoyable," an interactive digital learning medium developed using Wordwall, featuring games, leaderboards, and a point-based reward system. The research results show that this medium is valid according to material experts and media experts, practical based on teacher and student responses, and effective in increasing learning motivation and material understanding. Validation scores range from 88% to 90%, while practicality and effectiveness scores range from 82% to 92%. This medium enhances student engagement through enjoyable interactive learning while maintaining the essence of Al-Qur'an values. The study recommends a blended learning approach and the development of contextual content to optimize the use of Wordwall-based Al-Qur'an learning medium. Thus, QurFast is feasible and effective as a gamified Al-Qur'an learning medium.